Evaluation of the effect of two corn herbicides on nitrification in the soils - ADEBAYO, A.; FADAYOMI , O.; SALAWU, R. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
Two corn herbicides commonly in use in Nigeria namely cyanazine: 2[(4-chloro-6-(ethylamino)-s-triazine-2-yl) amino -2-] methylpropionitrite and atrazine: 2-chloro-4-(ethylamino)-6-(isopropylamino)-s-triazine were evaluated under greenhouse conditions to assess their effects on nitrification in soils at 3.0 and 6.0-kg/ha a.i. For the two soils used and the two herbicides, there was no evidence that the application of the herbicides at any of the rates inhibited nitrification irrespective of whether the soils were copped or uncropped. In fact, there was a slight enhancement of nitrification. If this is a true trend under field conditions, it could suggest that the use of these herbicide under Nigerian conditions might be serving a dual purpose of controlling the weeds and promoting nitrification in soils.